Conceptualizing Historical Legacies. (May 2015) - Wittenberg, Jason
In the nearly quarter century since the collapse of communism, a great many outcomes in East Europe and the former Soviet Union, from patterns of democratic consolidation to state–society relations, have been attributed to legacies of the past. Yet despite the common goal of understanding the influence of the past, there is little consensus on how to conceptualize historical legacies. Through a focus on post-communist outcomes and their relation to prior outcomes and causal precursors, this article assesses what counts as a historical legacy and how legacies differ from non-legacies.